The Potential of Corncobs in Producing Reduced Graphene Oxide as a Semiconductor Material - Kusuma Wardhani Mas'udah; Ahmad Taufiq; Sunaryono Sunaryono (Journal of Engineering and Technological Sciences, 2022)
A simple chemical approach was developed to synthesize reduced graphene oxide (RGO) from corncob waste through the acid-base method with the addition of PEG-2000 at specific concentrations. The morphology and structure of RGO were characterized by scanning electron microscopy and energy-dispersive X-ray spectroscopy. The process of reduction and quality of RGO were examined carefully with UV-Vis spectroscopy, infrared spectroscopy, and X-ray diffractometry. Based on the treatment and characterization, the diffraction data showed a prominent peak of RGO at a 2-theta position of 24.01°. The existence of C=C functional groups was detected in aromatic compound groups and alkene functional groups in aliphatic hydrocarbon compounds by infrared spectroscopy. The use of corncobs as the main raw material synthesized by an environmentally friendly route has tremendous potential in producing RGO that can be used as an efficient semiconductor material.